2018
DOI: 10.1007/s00436-018-5829-3
|View full text |Cite
|
Sign up to set email alerts
|

Integrated morphologic and molecular analysis of Trichomonas vaginalis, Mycoplasma hominis, and human papillomavirus using cytologic smear preparations

Abstract: Pathogenic microbes may colonize the female genital tract via sexual transmission and cause health issues like inflammation or malignancy, summarized as sexually transmitted disease (STD). A major representative of such pathogens is Trichomonas vaginalis (T.v.), whose role in the etiology of cervical cancer remains elusive. Traditional morphologic screening of cervical smears is able to detect T.v., although its identification may be complicated by look-alikes such as degenerated granulocytes and basal cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…Different screening strategies for women in different stages are good for earlier diagnosis of disease and cost saving for medical resources. In our study, only MH showed a significant positive association with hrHPV, as previously described, 21,22 although these previous studies could not rule out reverse causation. We did not find that MH infection was related to cervical carcinogenesis.…”
Section: Discussionsupporting
confidence: 58%
“…Different screening strategies for women in different stages are good for earlier diagnosis of disease and cost saving for medical resources. In our study, only MH showed a significant positive association with hrHPV, as previously described, 21,22 although these previous studies could not rule out reverse causation. We did not find that MH infection was related to cervical carcinogenesis.…”
Section: Discussionsupporting
confidence: 58%
“…39 Although we used only FFPE blocks-derived from HGSOC primary histology samples and peritoneal metastases processed as CBs-and identical IHC protocols to minimize technical variations and make our findings comparable, specimen handling could still differ in any step of this study or during the previous routine diagnostic preparation (e.g., duration of fixation), potentially impacting our results. Although cytology generally provides excellent material for IHC and molecular testing, 8,40 CB cytology samples in this study showed lower tumor cellularity than their paired histology, albeit both exhibiting adequate numbers of cancer cells for analysis (at least 100 cancer cells in all examined cases were needed as an inclusion criterion). This could have affected the subsequent IHC interpretation.…”
Section: Discussionmentioning
confidence: 77%
“…Studies have shown that a previous history of infection with TV leads to an increased risk of HPV infection, which is mainly due to the types of viruses with a high oncogenic risk [ 19 , 20 ]. It was also shown that HPV is a risk factor for TV, indicating a possible cooperation between these microorganisms that contributes to changes in the cellular microenvironment [ 21 ]. The TV, through the release of lytic enzymes, leads to the reduction of the mucous layer of the vaginal wall and, thus, the reduction of vaginal fluids.…”
Section: Discussionmentioning
confidence: 99%